A New Process for the recovery of bio-accumulated cadmium from Scallops - Ghimire, Kedar Nath (Journal of Nepal Chemical Society, 2013)
A novel process for cadmium recovery from mid gut of scallops is investigated based on the systematic information of the process system. Adsorption of cadmium was accompanied according to the cation exchange mechanism and the equilibrium pH increased to around 7 due to the isomorphous substitution of cadmium with that calcium of SAJR. A complete recovery of cadmium has been achieved from the process that we have developed from this study.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9337Journal of Nepal Chemical Society Vol. 30, 2012 Page:  62-65 Uploaded date: 12/16/2013